Whole-transcriptome analyses of Sorghum leaves identify key mRNAs and ncRNAs associated with GA3-mediated alleviation of salt stress - Wu, Yanqing; Liu, Jiao; Zhou, Guisheng (Frontiers in Plant Science, 2022)
Sorghum has attracted much attention in recent years for its tolerance in high salt environments. However, the effect and regulatory mechanism of the gibberellic acid (GA3)-mediated alleviation of salt stress in sorghum remains unclear. Herein, we reported that a GA3 concentrations of 50 mg/L is optimal for sorghum (“Jitian 3”) development under salt stress. We conducted a whole-transcriptome analysis between GA3-treated and control sorghum leaves under salt stress, and we identified 1002 differentially expressed (DE)-mRNAs, 81 DE-lncRNAs, 7 DE-circRNAs, and 26 DE-miRNAs in sorghum following GA3 treatment. We also identified a majority of DE-mRNAs and DE-ncRNAs targets that serve essential roles in phenylpropanoid biosynthesis and plant hormone networks. In addition, we generated a ceRNA-miRNA-target gene network, and 3 circRNAs (circRNA_2746, circRNA_6515, circRNA_5622) and 4 lncRNAs (XR_002450182.1, XR_002452422.1, XR_002448510.1, XR_002448296.1) probably acts as valuable candidates for the regulation of the GA3-mediated alleviation of salt stress in sorghum. Our findings uncovered potential mRNA and non-coding RNAs that contribute to GA3 regulation, thus offering a basis for the future investigation of underlying mechanisms of salt stress in sorghum.